2019
DOI: 10.1177/0883073819887590
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Stroke Impairs Theory of Mind Performance

Abstract: Aim: This pilot study explored whether childhood stroke impairs performance on theory of mind (ToM) tasks and whether ToM task performance correlates with resting state connectivity in brain regions linked with social cognition. Method: We performed a case-control study of 10 children with stroke and 10 age- and gender-matched controls. They completed 2 ToM tasks, and resting state connectivity was measured with functional magnetic resonance imaging (MRI). Results: Children with stroke performed worse than con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Studies indicate that theory of mind and psychosocial functioning are impaired after stroke. 22 , 23 The insult has been assumed to affect several social cognitive domains, probably regardless of stroke characteristics. 23 Although autism cannot be acquired later in life and the main cause of autism is considered genetic, stroke might be an additional factor for reaching the turning point because autism has multiple and complex causes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that theory of mind and psychosocial functioning are impaired after stroke. 22 , 23 The insult has been assumed to affect several social cognitive domains, probably regardless of stroke characteristics. 23 Although autism cannot be acquired later in life and the main cause of autism is considered genetic, stroke might be an additional factor for reaching the turning point because autism has multiple and complex causes.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, other studies have reported impaired theory of mind and cognitive deficits affecting psychosocial functioning in both children and adults who had a stroke. 22,23 Several studies have found an association between epilepsy of different etiologies, especially genetic, and autism, 24,25 leading to the assumption that both disorders are based partly on an impaired balance between inhibition and excitation. 26 An ischemic stroke that occurs before the affected motor function develops often results in cerebral palsy (CP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While characterizing ToM impairments is challenging, it is clear that executive functioning skills and ToM appear to mediate the relationship between TBI and social adjustment [ 52 ]. Similarly, children with arterial ischemic stroke (AIS) demonstrate difficulties with cognitive, affective, and conative ToM [ 53 , 54 ]. Adding to the complexity, a number of studies have identified broader executive functioning skills as playing an important role in peer acceptance and social competence for youth with a history of ABI [ 55 ], and peer-reported sociability and prosociality, as well as teacher-reported prosociality, positively mediate the relationship between executive functioning and peer acceptance, whereas social ostracism/victimization negatively mediate the relationship.…”
Section: Social Outcomes In Youth Following Abimentioning
confidence: 99%
“…Another small study of children with both IS and HS found impairments in aspects of Theory of Mind-the ability to take someone else's perspective. 46 Impairment in Theory of Mind is a hallmark feature of autism spectrum disorder (ASD). Studies examining the rates of ASD in pediatric stroke are limited and have documented relatively low rates (1%-2%) in mixed samples of perinatal/ childhood stroke.…”
Section: Social Cognitionmentioning
confidence: 99%